2010
DOI: 10.1111/j.1365-2966.2009.16132.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamo processes in the T Tauri star V410 Tau

Abstract: We present new brightness and magnetic images of the weak‐line T Tauri star V410 Tau, made by using data from the Narval spectropolarimeter at Télescope Bernard Lyot (TBL). The brightness image shows a large polar spot and significant spot coverage at lower latitudes. The magnetic maps show a field that is predominantly dipolar and non‐axisymmetric with a strong azimuthal component. The field is 50 per cent poloidal and 50 per cent toroidal, and very little differential rotation is apparent from the magnetic i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
72
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 50 publications
(85 reference statements)
13
72
2
Order By: Relevance
“…The probable absence of a radiative core and the non-detection of differential rotation in this work and other investigations Skelly et al 2010) leaves not much room for speculation about the nature of the dynamo operating in the interior of V410 Tau -at least in the framework of classical mean field dynamos. As has been shown by Küker & Rüdiger (1999) a likely explanation for the generation of the magnetic field in WTTS can be given in terms of a α 2 -dynamo.…”
Section: The Magnetic Nature Of V410 Taumentioning
confidence: 94%
See 4 more Smart Citations
“…The probable absence of a radiative core and the non-detection of differential rotation in this work and other investigations Skelly et al 2010) leaves not much room for speculation about the nature of the dynamo operating in the interior of V410 Tau -at least in the framework of classical mean field dynamos. As has been shown by Küker & Rüdiger (1999) a likely explanation for the generation of the magnetic field in WTTS can be given in terms of a α 2 -dynamo.…”
Section: The Magnetic Nature Of V410 Taumentioning
confidence: 94%
“…In a recent magnetic investigation of V410 Tau Skelly et al (2010) found that 50% of the total field has a toroidal component and the other 50% are poloidal and that the majority of the field shows strongly inclined large-scale azimuthal fields which are distributed over one entire hemisphere, whereas our reconstructed topology has only 27% toroidal fields and 73% poloidal fields with a strong radial and bipolar component around the polar region. Moreover, in contrast to our reconstructed maps where the strong magnetic fields are well correlated with the temperature, see Fig.…”
Section: The Magnetic Nature Of V410 Taumentioning
confidence: 96%
See 3 more Smart Citations